Salvaging empire : sovereignty, natural resources, and environmental science in the South Atlantic - Blair, James J. A., 1984- (Cornell University Press, 2023)
"Drawing on ethnographic and historical field research in the Falklands, Argentina and the UK, this book argues that by claiming self-determination and consenting to British sovereignty, the Falkland Islanders have crafted a settler colonial protectorate to extract resources and extend empire in the South Atlantic"-